Gold Doping of Silver Nanoclusters: A 26‐Fold Enhancement in the Luminescence Quantum Yield. (6th April 2016) - Soldan, Giada; Aljuhani, Maha A.; Bootharaju, Megalamane S.; AbdulHalim, Lina G.; Parida, Manas R.; Emwas, Abdul‐Hamid; Mohammed, Omar F.; Bakr, Osman M.
Abstract: A high quantum yield (QY) of photoluminescence (PL) in nanomaterials is necessary for a wide range of applications. Unfortunately, the weak PL and moderate stability of atomically precise silver nanoclusters (NCs) suppress their utility. Herein, we accomplished a ≥26‐fold PL QY enhancement of the Ag29 (BDT)12 (TPP)4 cluster (BDT: 1, 3‐benzenedithiol; TPP: triphenylphosphine) by doping with a discrete number of Au atoms, producing Ag29− x Au x (BDT)12 (TPP)4, x =1–5. The Au‐doped clusters exhibit an enhanced stability and an intense red emission around 660 nm. Single‐crystal XRD, mass spectrometry, optical, and NMR spectroscopy shed light on the PL enhancement mechanism and the probable locations of the Au dopants within the cluster.